2020
DOI: 10.3390/v12030285
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions Between HBV and the Innate Immunity of Hepatocytes

Abstract: Hepatitis B virus (HBV) infection affects ~350 million people and poses a major public health problem worldwide. HBV is a major cause of cirrhosis and hepatocellular carcinoma. Fewer than 5% of HBV-infected adults (but up to 90% of HBV-infected infants and children) develop chronic HBV infection as indicated by continued, detectable expression of hepatitis B surface antigen (HBsAg) for at least 6 months after the initial infection. Increasing evidence indicates that HBV interacts with innate immunity signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 93 publications
(81 reference statements)
0
46
0
Order By: Relevance
“…MAVS then links RIG-I to IKKi and TBK1 activation. The role of MAVS/IPS-1 is essential for induction of IFN by cytosolic DNA [ 132 , 133 ].…”
Section: Viral Infections and Mitochondrial Biogenesismentioning
confidence: 99%
“…MAVS then links RIG-I to IKKi and TBK1 activation. The role of MAVS/IPS-1 is essential for induction of IFN by cytosolic DNA [ 132 , 133 ].…”
Section: Viral Infections and Mitochondrial Biogenesismentioning
confidence: 99%
“…Hepatitis B virus (HBV), a member of the Hepadnaviridae family, is one of the smallest enveloped animal DNA viruses and the pathogen to cause Hepatitis B. Although HBV vaccines and effective antiviral drugs have been available for more than 20 years, chronic HBV infection (CHB) remains a global public health problem, especially in Asia ( Megahed et al, 2020 ). Increasing attention has been paid to the relationship between HBV infection and hepatic lipid metabolism recently.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic HBV infection is a global public health threat; millions of people suffer chronic infection with the virus (1). Previous studies have shown that HBV behaved like a "stealth" virus that establishes persistent infection in hepatocytes (16)(17)(18). Whether or not HBV stimulates and interferes with innate immune responses has been a matter of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…HBV behaves like a "stealth" virus that establishes persistent infection in hepatocytes using multiple evasion strategies to suppress host innate and adaptive immune systems (16)(17)(18). Almost all HBV proteins interfere with intracellular signal transduction pathways, such as IFN associated signaling pathways and inflammation-related pathways (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%